ANALISIS YURIDIS PUTUSAN PELANGGARAN MEREK TERKENAL BERDASARKAN PUTUSAN MAHKAMAH AGUNG REPUBLIK INDONESIA NOMOR. 595 K/PDT.SUS/2011 TERHADAP KASUS PT. SINDE BUDI SENTOSA DAN WEN KEN DRUG CO PRIVATE LIMITED (PTE LTD) - Tiara Rahma Syafitr; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2015)
The progress of science and technology in the field of electronic, telecommunication and transportation allowing a variety of information takes place very rapidly, accurate, efficient and effective for the industrial world in the field of intellectual property rights, especially in the field of brand.Therefore, needed a legal protection of trademarks, especially to the famous brand. As known from the TRIPS agreement was approved and ratified by Indonesia, Indonesia must devise a National laws in the field of Intellectual Property Rights, including the brand with the existing provisions in the TRIPS Agreement. In the Law on Marks is currently in effect, the authority to protect the famous brands granted by Article 4, Article 5, Article 6 paragraph (1) letter b, and Article 6 paragraph (2) The Law No. 15 of 2001 on Marks. famous brand owners who have not registered in Indonesia can show evidence of fame trademark by filing a trademark registration cancellation through the Commercial Court under Article 4, Section 5, and Section 6 The Law No. 15 of 200 about the brand. The Law No. 15 of 2001 on Marks has not fully protect famous brand which has not been registered. The Law No. 15 of 2001 on Marks authorize the relevant authorities namely the Directorate General of Intellectual Property Rights in this case Directorate brand, to protect famous brand by refusing registration of the mark containing the equation either substantially or wholly with famous brand owned by other parties, especially for goods and / or services. In the Law on Marks is currently in effect, the authority to protect the famous brands granted by Article 4, Article 5, Article 6 paragraph (1) letter b, and Article 6 paragraph (2) The Law No. 15 of 2001 on Marks. famous brand owners who have not registered in Indonesia can show evidence of fame trademark by filing a trademark registration cancellation througt the Commercial Court under Article 4, Section 5, and Section 6 The Law No. 15 Year 2001 on the marks. Based on the results of the formulation of the problem, it can be concluded that the judge in decisions just look at the arguments put forward by PT. Sinde Budi Sentosa without considering the arguments put forward by Wen Ken Drug Co. Private Limited as the first user trademark Cap Three Legs Toning solution with Rhino Painting used and published in the daily news of Singapore since 1937 and wrong within implementing rules of evidence ownership of the Marks, so that the non-fulfillment of legal certainty and the norms of justice. Advice of the author, should The Law No. 15 of 2001 on Marks can be renewed by seeing the development of world trade, especially in the field of Famous Brands to avoid the parties in bad faith without the use of the right to use the Famous Brand.Keywords: Famous-Brand Trademark Infringement-Supreme Court Decision